PENGARUH FINANCIAL DISTRESS, LIQUIDITY RATIO, DAN FIRM SIZE TERHADAP PENERAPAN HEDGING - Wiranda, Nadya Ade; Rahim, Rida (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
This research was conducted aiming to find out the factors that influence the use of derivative instruments in the application of hedging policies in manufacturing companies in the Indonesia Stock Exchange for the period 2015 to 2018. Independent variables in this study include financial distress, liquidity ratio, and firm size, while hedging is used as the dependent variable. This research using purposive sampling technique and 103 companies are used as research samples. The data analysis used in this study is logistic regression, where the results obtained, liquidity ratios have a significant and negative effect then financial distress and size variables have a significant effect and are positive. Keywords : hedging, instrument derivatives, financial distress, liquidity ratio, size